2017
DOI: 10.18410/jebmh/2017/117
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Johnson’s Formula, Insler’s Formula and Hadlock’s Formula for Estimating Foetal Weight at Term

Abstract: BACKGROUND Foetal weight is one of the greatest factor determining the survival of the foetus. Estimation of foetal weight predelivery helps to decide the mode of delivery and anticipate problems during labour. Aim of the study is to assess the foetal weight in term pregnancies by various methods, i.e. abdominal girth x symphysiofundal height (Insler's Formula), Johnson's formula and Hadlock's formula using USG to study the accuracy of these methods and to correlate these methods of estimation of foetal weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The results corroborate with that the study of Nayak and others which reported that prediction of fetal weight by clinical method was as accurate as the ultrasonographic method. 16 Majority of the studies including the present study reported USG was superior to clinical method in estimating fetal weight in terms of percentage error. 1,17 On the other hand, a few studies showed that clinical method has the same accuracy or even better than USG.…”
Section: 15mentioning
confidence: 62%
See 1 more Smart Citation
“…The results corroborate with that the study of Nayak and others which reported that prediction of fetal weight by clinical method was as accurate as the ultrasonographic method. 16 Majority of the studies including the present study reported USG was superior to clinical method in estimating fetal weight in terms of percentage error. 1,17 On the other hand, a few studies showed that clinical method has the same accuracy or even better than USG.…”
Section: 15mentioning
confidence: 62%
“…15 As reported by Nayak and others the results of the study also showed that least average error was observed with USG while least standard error was observed with Dare's formula and the values were closer between USG and Dare's method. 16 Comparison results showed that both USG and Dare's predictions are closer to the actual baby weight and hence Dare's method can be considered an alternative method in the absence of USG. The results corroborate with that the study of Nayak and others which reported that prediction of fetal weight by clinical method was as accurate as the ultrasonographic method.…”
Section: 15mentioning
confidence: 95%
“…8 However, Nayak et al conducted a study which showed that the fetal weight estimation the clinical method was as accurate as of the ultrasound method. 18 Some studies have shown that the clinical method has the same accuracy or even better than USG. 19,20 This study has shown that the ultrasound method of fetal weight estimation was more accurate than the clinical estimation of fetal weight estimation which is similar to the studies done by Ugwa et al and Chauhan and coworkers.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal weight in conjuction with gestational age is an important indicator of pregnancy outcome. 2 Two main methods for predicting birth-weight in current obstetrics were used: (a) Clinical techniques based on abdominal palpation fetal parts and calculations based on fundal height and (b) Sonographic measures of skeletal fetal parts, which are then inserted into regression equations to derive estimated fetal weight. 3 Evaluation of uterine size externally with use of a physician's hand is characterized by being simple, easy and cheap.…”
Section: Introductionmentioning
confidence: 99%